PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE QUESTIONS STUDENTS HAVE (QSH) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PASAMAN - Andesta, Elfisa Delfia; Rahmi, Rahmi; Harisman, Yulyanti (Pendidikan Matematika, 2013)
This research is motivated by the lack of understanding of the mathematical concepts that students learn mathematics and results from class VIII student SMPN 1 Pasaman. Students did not dare to ask verbally of subject matter is not understood. This study aims to determine, whether the students understanding of mathematical concepts by implementating a strategy type Questions Students Have better than students understanding of mathematical concepts with conventional learning of studentâs class VIII SMPN 1 Pasaman School Year 2012/2013, and to determined whether the implementation of strategy type Questions Students Have effectively in the learning of mathematics. Type of research is experimentalâs research with random design of subject. The research instrument is shaped essay with a final test of reliability is 0,85, and questionnaire research with criteria very effective is 82,26%. Based on hypothesis test results obtained p-value is 0,028 less than the specified Â is 0,05, then reject H0. So, it can be concluded that the students understanding of mathematical concepts by implementating a strategy type Questions Students Have better than students understanding of mathematical concepts with conventional learning at the level of 95%. Questionnaire data analysis showed that the application of strategy type Questions Students Have is very effective in learning mathematics.